2013
DOI: 10.5130/csr.v9i1.3591
|View full text |Cite
|
Sign up to set email alerts
|

Fictocritical Empathy and the Work of Mourning

Abstract: What is at stake in this fictocritical aesthetic remediation? What existing practices would it re-function, supplement or supersede? Is mourning adequate to the task of cross-cultural reconciliation? How might fictocritical effects be animated in the service of this aim? In the process of exploring these questions I will suggest that the methodology of mourning is an allegorical vehicle for cross-cultural writing. Employed to remediate the colonial inheritance, it nonetheless requires acts of empathy according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Such contingencies are central to cultural studies, which also examines social mechanisms for channeling or blocking empathy. Additionally, ethnomusicology has offered imagined or anticipated empathy (Abe, 2013), game studies has presented empathy toward electronic avatars (Collins, 2011), and postcolonial literary criticism has critiqued empathy as an individualist construct imbricated in power relations (Kerr, 2003).…”
Section: Intimacy Affect Empathymentioning
confidence: 99%
See 1 more Smart Citation
“…Such contingencies are central to cultural studies, which also examines social mechanisms for channeling or blocking empathy. Additionally, ethnomusicology has offered imagined or anticipated empathy (Abe, 2013), game studies has presented empathy toward electronic avatars (Collins, 2011), and postcolonial literary criticism has critiqued empathy as an individualist construct imbricated in power relations (Kerr, 2003).…”
Section: Intimacy Affect Empathymentioning
confidence: 99%
“…Relational-cultural theory posits a mutual, two-way empathy as part of social change (Comstock et al., 2008). Kerr (2003) similarly describes the perspective of empathy as an ongoing process of oscillation between self and other, between looking at the other as object and as self-identified-with-an-other. Hollan (2012), in reviewing cross-cultural studies of empathy, writes that “empathy is never ‘neutral,’ but rather is always found embedded in a moral context” and describes an “emotional resonance” that can lead to “a helping or care-taking gesture” (p. 72).…”
Section: Intimacy Affect Empathymentioning
confidence: 99%
“…18 Witnessing the direction that cross--cultural fictocriticism has taken, it would seem that Gibbs's call has been answered, as it purports to rely 'on a politicised sentimental imagination that aims to enhance our capacity to be affected by the effects of history'. 19 Fictocriticism, perhaps more than any other genre, has been involved from the start in a systematic critique of its own formal and ideological foundations as well as of the relationship between reader and work. In the hands of some practitioners, it has also helped to question the binary thinking that draws a clear--cut line between creative and critical material while undermining what the American poet Bob Perelman once described as the 'Manichean model of / a prosy command--centre of criticism and / unique bivouacs on the poetic margins'.…”
mentioning
confidence: 99%